6/36, 5/30
these two are proportional, hope this helpsss
Answer:
y = 1
Step-by-step explanation:
4 - (y-3) = 3(y+1) - 4(1 - y)
4 -y +3 = 3y + 3 - 4 + 4y
7 - y = 7y - 1
7 + 1 = 7y + y
8 = 8y
8/8 = y
Answer:
B.
Step-by-step explanation:
Range is all the set y values.
Using subtraction of perfect squares, it is found that the factored expression is:
9t² - 4 = (3t - 2)(3t + 2).
<h3>What is the subtraction of perfect squares factoring?</h3>
It is given as follows:
a^2 - b^2 = (a - b)(a + b)
In this problem, the binomial is given as follows:
9t² - 4.
Hence:
Hence the factored expression is:
9t² - 4 = (3t - 2)(3t + 2).
More can be learned about subtraction of perfect squares at brainly.com/question/16948935
#SPJ1